2021
DOI: 10.1128/aac.01436-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity and In Vivo Efficacy of Cefiderocol against Stenotrophomonas maltophilia

Abstract: Cefiderocol is a novel siderophore cephalosporin antibiotic with broad coverage against difficult-to-treat Gram-negative bacteria, including those resistant to carbapenems. Its activity against Stenotrophomonas maltophilia was investigated in vitro against clinical isolates and in lung infection models using strains either resistant (SR202006) or susceptible (SR201934, SR200614) to trimethoprim/sulfamethoxazole. Cefiderocol demonstrated potent in vitro activity against all 217 S. maltophilia clinical isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
0
17
0
3
Order By: Relevance
“…Twenty-five studies investigated the characteristics of PK and/or PD of cefiderocol ( Katsube et al, 2016 ; Katsube et al, 2017 ; Matsumoto et al, 2017 ; Monogue et al, 2017 ; Ghazi et al, 2018a ; Ghazi et al, 2018b ; Katsube et al, 2018 ; Kawaguchi et al, 2018 ; Saisho et al, 2018 ; Katsube et al, 2019a ; Kidd et al, 2019a ; Katsube et al, 2019b ; Kidd et al, 2019b ; Chen et al, 2019 ; Miyazaki et al, 2019 ; Nakamura et al, 2019 ; Stainton et al, 2019 ; Matsumoto et al, 2020 ; Ota et al, 2020 ; Gill et al, 2021 ; Katsube et al, 2021 ; Kawaguchi et al, 2021 ; Kobic et al, 2021 ; König et al, 2021 ; Nakamura et al, 2021 ). A phase I study including healthy Japanese and Caucasian volunteers showed exhibit linear PK at doses of up to 2,000 mg, with low to moderate interindividual variability ( Saisho et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-five studies investigated the characteristics of PK and/or PD of cefiderocol ( Katsube et al, 2016 ; Katsube et al, 2017 ; Matsumoto et al, 2017 ; Monogue et al, 2017 ; Ghazi et al, 2018a ; Ghazi et al, 2018b ; Katsube et al, 2018 ; Kawaguchi et al, 2018 ; Saisho et al, 2018 ; Katsube et al, 2019a ; Kidd et al, 2019a ; Katsube et al, 2019b ; Kidd et al, 2019b ; Chen et al, 2019 ; Miyazaki et al, 2019 ; Nakamura et al, 2019 ; Stainton et al, 2019 ; Matsumoto et al, 2020 ; Ota et al, 2020 ; Gill et al, 2021 ; Katsube et al, 2021 ; Kawaguchi et al, 2021 ; Kobic et al, 2021 ; König et al, 2021 ; Nakamura et al, 2021 ). A phase I study including healthy Japanese and Caucasian volunteers showed exhibit linear PK at doses of up to 2,000 mg, with low to moderate interindividual variability ( Saisho et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro PK/PD study showed that the standard dose could completely kill meropenem-resistant gram-negative isolates showing cefiderocol MICs of 0.5–4 g/ml within 24 h ( Matsumoto et al, 2020 ). Nine animal studies using neutropenic murine thigh models or respiratory tract infection models mimicking humanized exposures (2g q8h with a 3-h infusion) showed a >1 log 10 reduction in bacterial colony forming units (CFU) of most Gram-negative bacteria with MICs ≤4 g/ml, but not for the isolates with MICs ≥ 8 mg/L ( Supplementary Table S1 ) ( Matsumoto et al, 2017 ; Monogue et al, 2017 ; Ghazi et al, 2018b ; Kidd et al, 2019b ; Chen et al, 2019 ; Stainton et al, 2019 ; Ota et al, 2020 ; Gill et al, 2021 ; Nakamura et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…All 94 isolates tested in our study were susceptible to minocycline. Recently, the United States Food and Drug Administration (FDA) and the European Medicines Agency (EMA) approved a new drug, cefiderocol, which also presents high activity against S. maltophilia strains [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although all 3 isolates had cefiderocol MICs of 0.25 mg/L, bactericidal activity achieved by 8 hours and sustained through 24 hours was subsequently lost as regrowth and the development of resistant mutants (MIC >64 mg/L) was observed by 72 hours against all strains. Despite this relatively poor in vitro activity in static and dynamic PK/PD models, cefiderocol has demonstrated excellent in vivo activity against S maltophilia in neutropenic and immunocompetent mouse and rat thigh and lung infection models [ 28 , 48 , 49 ]. Importantly, the efficacy of cefiderocol was equal to or better than that of comparator agents such as ceftazidime, levofloxacin, and minocycline and was not impacted by resistance to these agents.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%